Molecular profiling of four virulence-related genes of enteroaggregative escherichia coli isolates from Ospital ng Makati, Makati City, Philippines - Cabal, Ace Bryan S. (2013)
Enteroaggregative Escherichia coli (EAEC) is an emerging enteric pathogen that causes acute and chronic diarrhea and malnutrition among children, adults and those that are immunocompromised individuals in developing countries. It is also regarded as a leading cause of bacterial diarrhea in developed countries. There was no single EAEC-associated virulence gene or virulence gene combinations that have been evaluated as a tool for identification of EAEC. Moreover, no single or combinations of virulence genes have been found to be present in all EAEC strains thus, EAEC is considered as a very heterogenous pathotype of E.coli in terms of pathogenic potential. This study aimed to characterize the molecular profile, occurrence and relatedness of the four virulence-related genes of EAEC, namely, aggR and aap, which are plasmid-encoded genese and pic andaaiA, which are chromosome-encoded genes among 100 E.coli isolated from Ospital ng Makati. The isolates were subjected to real-time PCR to detect the four target virulence markers and the identity was confirmed through DNA sequencing. Phylogenetic analyses were also performed to describe the clonal relatedness of the four virulence-related genes. Among the 100 E.coli isolates tested for the four EAEC virulence-related genes, 20 (20%) turned out to be negative for the all of virulence markers. In contrast, 80/100 (80%) isolates were positive for at least one virulence-related genes. Nine percent (9%) were revealed to be carrying aggR, aap, pic and aaiA. The heterogenous grouping of the four virulence-genes presented in this report, shows multi-ancestral origin of the genes and random genetic recombination of virulence determinants. The data presented in this paper further validate previously published reports on the heterogeneity and varying pathogenicity of EAEC isolates based on the occurrence nof its chromosomal and plasmid-borne virulence-related genes.
Thesis (MS Public Health, Medical Microbiology)--University of the Philippines Manila
Keywords: Escherichia coli; Diarrhea in children